Spatial and Temporal Distribution of Near-Surface Methane Concentration in Northwest China Based on GOSAT Satellite Data. (1st March 2023) - Lian, Haotian; Shi, Xiaoqi; Shen, Yufei; Wang, Chuyu
Abstract: Methane (CH4 ) is a common greenhouse gas that plays an important role in global warming and affects people's production and life. In order to study the temporal and spatial distribution situation of methane concentration in northwest China (Shaanxi, Gansu, Ningxia, Xinjiang, Qinghai), this article used L4B level data products monitored by GOSAT satellite from 2009 to 2019 to study the temporal and spatial distribution characteristics of near-surface methane concentration in northwest China. The results of the analysis were as follows. Firstly, the annual average concentration of near-surface methane in northwest China was in a rising state, and the maximum annual average concentration increment was in 2016. Secondly, seasonal variation of methane concentration: Autumn>Summer>Spring>Winter. Finally, spatial variation of the annual average methane concentration: Shaanxi, Ningxia, and southern Gansu>northwest Xinjiang>other northwest China regions. The methane concentration decreased from the bottom to the top gradually.